Masked by Fire: A Pilot Study Analyzing Perimortem Ballistic Trauma in Burnt Remains - Rundle, Jarred (University of Waterloo, 2015)
Fire is believed to destroy everything it comes into contact with, making it a popular choice for covering up crimes like murder. By warping and shrinking the bones, fire can pose quite a challenge to even the most experienced forensic investigator. To better understand the effects of fire on bodies it is common for forensic investigators to set up experiments to study these effects. In the case of my thesis I employed an experiment to look at the effects fire can have on remains that have been inflicted with ballistic trauma. Through careful examination of the skeletal remains, I have attempted to observe the morphological changes of the traumatic markers on the bones as they progress through the different stages of burning. It is my hope that my research will provide forensic investigators with a better understanding of how ballistic trauma changes in fire and how to identify the differences between the postmortem fractures of fire to the perimortem fractures generated by ballistic trauma.
Keywords: Forensic Anthropology; Burnt Remains; Trauma Analysis; Public Issues Anthropology